Using Different Angles of Rotating Blades Using the Finite Element Method - Hassan Ali Hassan; Ahmad Soheili Mehdizadeh (Journal of Techniques)
One of the most important operations in agriculture is tillage, which has a great contribution to increasing crop yield and aeration of the soil and, ultimately, root development. Among the important tools for tillage are rotary rotators that are exposed to high and variable dynamic loads, so they are designed to have both the greatest contribution to soil agitation and high strength; It is necessary. Therefore, in this research, an L-shaped blade sample was designed for a rotator using a Biomimetic method. Due to the extensive research that has been done in the world in the field of manufacturing different types of rotators with a rotating agitator mechanism, therefore, it is necessary to study and optimize the rotator blades according to Iranian conditions. In this study, the studied variables include dependent and independent variables. Dependent variables include von Mises stress and arm displacement, and independent variables include the dimensions and geometric parameters of the Shape of the Rotator Blades. The idea for the blade design was inspired by the paw of a mole rat. Six blades were designed by simple method and biomimetic method and then by finite element method. Effects of blade angle change and design method on stress distribution, maximum displacement, maximum energy absorbed in the blade, reliability and under 400 N checked out. The results showed that in all designed models, the values of stress, displacement and energy absorbed were lower in the biomimetic design mode. As the blade angle increased, the values of the above parameters also decreased. Finally, the best model for having the least von Mises stress and the highest reliability was the blade with a Biomimetic design and a 20-degree angle.